Increased plasma imatinib exposure and toxicity in chronically treated GIST patients with SARS-CoV-2 infection: a case series - Gagno, Sara; Posocco, Bianca; Orleni, Marco; Cecchin, Eleonora; Fumagalli, Arianna; Guardascione, Michela; Buonadonna, Angela; Polesel, Jerry; Puglisi, Fabio; Toffoli, Giuseppe; Cecchin, Erika (Frontiers in Immunology, 2024)
Introduction: Inflammatory factors released during severe coronavirus disease-19 caused by acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are known to influence drug exposure, but data on the effect of mild infection are few. Here we describe for the first time an increase in plasma imatinib and norimatinib concentrations observed in a series of 5 patients treated with imatinib for gastrointestinal stromal tumor (GIST) after mild COVID-19. Methods: The patients were undergoing routine therapeutic drug monitoring (TDM) and pharmacogenetic (PGx) analyses of polymorphisms in genes involved in imatinib metabolism and transport (CYP3A4, CYP3A5, ABCB1, and ABCG2) when SARS-CoV-2 infection occurred. Imatinib and its active metabolite norimatinib concentrations were determined at C trough using a validated LC-MS/MS method. PGx analyses were performed by KASP genotyping assays on a Real-Time PCR system. All patients received imatinib 400 mg/day. Case 1 was prospectively monitored. Cases 2-5 were identified retrospectively. Results: On average, imatinib C trough increased significantly by 70% during COVID-19, whereas norimatinib showed a 44% increase compared with pre-COVID-19 levels. Elevated plasma imatinib concentrations persisted up to 6 months after infection remission. In 3 cases, this increase reflected the occurrence or worsening of imatinib side effects. Conclusion: This case-series highlights the clinical impact of SARS-CoV-2 infection on the management of patients with GIST treated with imatinib.Abbreviations: SD, standard deviation; CRP, C-reactive protein; NA, not available; AGP, alpha-1 acid glycoprotein. * The pre-COVID-19 levels of imatinib and norimatinib were estimated as the average levels of two blood samples collected before COVID-19. ** The post-COVID-19 levels of imatinib and norimatinib were estimated as the average levels in blood samples collected when pre-COVID-19 concentrations were restored. ° data from a single sample taken 2 months after COVID-19. † in brackets is the percentage increase over pre-COVID-19 levels. #Based on the phenotype derived from the following CYP3A5 polymorphisms: rs776746 (*3) c.219-237G>A; rs10264272 (*6) c.624G>A; rs41303343 (*7) c.1035dup.